Evaluation of Strategies and Challenges in Implementing the Kampung KB Program in Bimomartani Village, Sleman, DIY - Rizky, Fadliana Hidayatu (BKM Public Health and Community Medicine, 2024)
Purpose: This study analyzes the strategies and challenges in implementing the Kampung Keluarga Berencana (KB) Program in Bimomartani Village, Sleman Regency. The primary focus is identifying obstacles and offering solutions to enhance the program's effectiveness. Methods: The study utilized a qualitative approach to gather data through interviews, observations, and document analysis, focusing on the implementation process and the challenges encountered. Results: The Kampung KB program, initiated by BKKBN, aims to control population growth and improve family welfare through an integrative approach encompassing population, family planning, and family development. The program's implementation in Bimomartani Village has shown positive impacts on the community, such as increased awareness and participation in family planning initiatives. However, several challenges were identified, including an ineffective organizational structure, a lack of human resources, unclear information dissemination, and a limited budget. Conclusion: Structural and operational reforms are necessary to enhance the coordination, information flow, and overall effectiveness of the Kampung KB program. Simplifying, clarifying, and making the organizational structure more flexible will address existing challenges and support the program's goals of improving family welfare and controlling population growth.